Performance, Carcas And Broiler Lives With Giving Miana (Coleus atropurpureus, L) Leaves Fermentation Drink - Malvin, Toni; Fati, Nelzi; Syukriani, Debby; Sari Amir, Yurni; Mohtar L, Ulva; Siregar, Ramond (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
The purpose of this study was to determine the effect of adding miana (Coleus atropurpureus, L) leaf fermented drink on performance, carcass and chicken liver. Broiler DOC without sexual segregation totaled 196 tails. The design used was a completely randomized design consisting of 4 treatments and three replications. Each test consisted of 16 tails. The treatments were: A0 = without fermented miana leaves, A1 = 4 ml fermented miana leaves /l drinking water, A2 = 8 ml fermented miana leaves/ l drinking water, A4 = 12 ml fermented miana leaves /l drinking water. The parameters observed were performance, percentage of carcass and chicken liver. The result showed that was no effect (P>0,05) of the addition of miana leaf fermentation on the performance, percentage of carcass and chicken liver. Offering 8 ml fermented miana leaves/liter provides better performance.